Comparative expression analysis of small intestine nutrient transporters sodium/glucose cotransporter 1 (SGLT1) and peptide transporter 1 (PepT1) between Itik Pinas (Anas platyrhynchos L.) and commercial layer chicken (Gallus gallus domesticus) - Pinca, Alexadrinne M; Bautista, herald Nygel F.; Adiova, Christine B.; Sangel, Percival P. (2019)
Itik Pinas (IP) is an improved breed of egg-type Philippine mallard duck (Anas platyrhynchos L.) that was developed to address the low egg production of the traditional mallard ducks. However, the improvement in genetic potential can only be realized if appropriate care and management – including feeding system – will be provided to the ducks. The energy and nutrient requirements of IP has yet to be established. Most IP raisers use commercial layer diets that are being formulated based on nutrient recommendations for chickens. However, differences in digestive physiology among poultry species might cause differences in their nutrient requirements. One way to better understand the digestive capacity and absorption efficiency of IP is to know the expression levels of nutrient transporter genes in their small intestine. Two nutrient transporters, specifically sodium/glucose cotransporter 1 (SGLT1) and peptide transporter 1 (PepT1), were analyzed from the small intestine of IP and were compared with those of layer chicken. Total RNA was independently isolated from the three main segments of the small intestine (i.e., duodenum, jejunum, and ileum) of IP-Kayumanggi and commercial layer chicken (CLC). The relative mRNA expression levels of the target genes from each of the intestinal segment in IP- Kayumanggi were assessed using real-time quantitative polymerase chain reaction (RT-qPCR) and were compared to the respective relative mRNA expression levels of the target genes in CLC. Results showed that SGLT1 has significantly higher relative mRNA expression levels in the three intestinal segments of IP-Kayumanggi compared to that in CLC. SGLT1 levels in IP were greatest in the ileum and jejunum. PepT1 relative mRNA expression levels in IP from the three intestinal segments, however, were shown to be comparable with that of CLC. Dissociation curve analysis showed a single peak, which validated the fidelity of the results. These novel findings suggest higher absorptive capacity of IP for monosaccharides, which may lead to higher energy value of feed ingredients for IP compared to CLC. Further studies must be conducted to determine the feeding value of feeds specific for IP.
Keywords: Ducks; Native duck, Itik Pinas; Egg production